2020
DOI: 10.1002/ags3.12338
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future of three‐field lymphadenectomy for thoracic esophageal cancer

Abstract: In spite of repeated appeal of the effectiveness of three‐field lymphadenectomy (3FL) by Japanese esophageal surgeons, it has not been accepted worldwide as a standard therapeutic measure for thoracic esophageal cancer. In this review, a concise summary of the history of 3FL, its present position, and its future perspective is discussed. Although a lack of randomized controlled trial (RCT) is one of the largest criticisms of 3FL, it seems difficult to make 3FL world‐standard even if a RCT with a positive resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…However, the range of LN dissection in resectable middle and lower thoracic ESCC remains controversial. Three-field lymphadenectomy has been widely accepted as a standard procedure for ESCC patients in Japan but is not yet the world standard [ 17 , 18 ]. Cervical LN metastases are common in ESCC patients, with a metastatic rate of at least 20 percent [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the range of LN dissection in resectable middle and lower thoracic ESCC remains controversial. Three-field lymphadenectomy has been widely accepted as a standard procedure for ESCC patients in Japan but is not yet the world standard [ 17 , 18 ]. Cervical LN metastases are common in ESCC patients, with a metastatic rate of at least 20 percent [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of 3-FL in Japan is due to the rapid increase in the number of laparoscopic esophagectomy for esophageal cancer in recent years [30]. Meta-analyses and studies comparing 3-FL and 2-FL reported a tendency for a better prognosis of the 3-FL group [31][32][33][34][35][36][37]. Ye et al [34] reported that 3-FL provides a better 5-year survival rate than 2-FL for thoracic esophageal cancer with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Japan where adenocarcinomas of the lower esophagus and esophagogastric junction are more prevalent than in Western countries, squamous cell carcinoma of the thoracic esophagus is the most common type of esophageal cancer. Traditionally, subtotal esophagectomy and three-field lymphadenectomy, including cervical lymphadenectomy, have been standard in Japan [ 18 ]. Additionally, to prevent recurrence after surgery, NAC rather than postoperative chemotherapy is administered in Japan, based on clinical trial results.…”
Section: Discussionmentioning
confidence: 99%